Cardiac Rehabilitation in Real Life - Jankowski, Piotr (Medicine (Baltimore), 2015)
Participation in cardiac rehabilitation programs (CRPs) improves prognosis in patients with coronary artery disease (CAD). However, not much is known about the effectiveness of CRP in real life. The aim of this analysis was to identify factors related to the referral to CRP following hospitalization for CAD and estimate the effectiveness of the programs in real life. Medical records of 1061 consecutive patients aged ≤80 years, hospitalized due to an acute coronary syndrome or for a myocardial revascularization procedure in 5 hospitals serving the city and surrounding counties, were reviewed and 611 patients were interviewed 6–18 months posthospitalization. Of 611 patients participating in the interview, 212 (34.7%) were referred following the hospitalization to a center providing CRP. Age, hospitalization in a teaching hospital, and index diagnosis were independently related to being granted a referral. Among the referred patients, 86.3% participated in the CRP. Participation in CRP was related to the lower probability of having high total cholesterol (23% vs 32%, P < 0.05), fasting glucose (11% vs 18%, P = 0.05), Hb(A1c) (8% vs 16%, P = 0.05), and body mass index (27% vs 37%, P < 0.05). Generally, the effect of the CRP was significant in participants with a higher education, but not in those with a low education level. Other factors were not significantly related to the effectiveness of CRP. This study shows that CRPs are effective, but underused in Poland. The participant's education level may influence the effectiveness of CRP. Therefore, in order to increase the impact of CRP, the content of such programs should vary depending on the education level of the participants.